A limbic circuitry involved in emotional stress-induced grooming - Ming-Dao Mu (Nature Portfolio, 2020)
Self-grooming is a frequently observed repetitive behaviour in rodents that is believed to contribute to post-stress de-arousal. The authors identified a previously unknown limbic circuit that includes the ventral lateral septum in rats and is involved in regulating stress-induced self-grooming.